2014
DOI: 10.1167/iovs.13-13762
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosoglutathione Inhibits Inducible Nitric Oxide Synthase Upregulation by Redox Posttranslational Modification in Experimental Diabetic Retinopathy

Abstract: In this study, a new therapeutic modality (GSNO eye drop) targeting nitrosative stress by redox posttranslational modification of iNOS was efficient against early damage in the retina due to experimental DR. The present work showed the potential clinical implications of balancing the S-nitrosoglutathione/glutathione system in treating DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In addition, liraglutide was able to prevent the diabetes-induced increase of caspase-8 and the Bax (proapoptotic)/Bcl-xL (antiapoptotic) ratio. In addition, we found that liraglutide (systemically and topically administered) was able to prevent the diabetes-induced retinal activation of p53, a factor that participates in hypoxic and oxidative stress-mediated retinal cell death (38), as well as several key molecules involved in retinal apoptosis and inflammation such as FasL and iNOS (39)(40)(41).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, liraglutide was able to prevent the diabetes-induced increase of caspase-8 and the Bax (proapoptotic)/Bcl-xL (antiapoptotic) ratio. In addition, we found that liraglutide (systemically and topically administered) was able to prevent the diabetes-induced retinal activation of p53, a factor that participates in hypoxic and oxidative stress-mediated retinal cell death (38), as well as several key molecules involved in retinal apoptosis and inflammation such as FasL and iNOS (39)(40)(41).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, iNOS serves an important role in leukostasis, apoptosis and BRB breakdown (27,28). Concurrently, white blood cells interact with, and bind to, ICAM-1 on the surface of endothelial cells in a multi-step process leading to adherence of the blood cells to the endothelial wall.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested inverse relationship between HO-1 and iNOS expression, where restoring HO-1 or carbon monoxide inhibits iNOS expression [31,32]. There is increasing evidence that iNOS is anti-angiogenic [18].…”
Section: Discussionmentioning
confidence: 99%